A hybrid heuristic technique for optimal coordination in intermodal logistics scheduling. (2017) - Chen, Cheng-Chieh; Schonfeld, Paul
This paper specifies a mixed integer nonlinear programming problem (MINLP) for assisting intermodal logistics operators with coordination decisions in freight transfer scheduling. An optimisation model is developed for coordinating vehicle schedules and cargo transfers at intermodal freight terminals, which is done primarily by optimising coordinated service frequencies and slack times, while also considering loading and unloading, storage and cargo processing operations. A hybrid technique combining sequential quadratic programming and genetic algorithms (GA-SQP) is developed to solve the proposed MINLP. This study also provides flexibility in managing general and perishable cargos with different cargo value functions that depend on dwell times. In a case study we derive insights which support intermodal logistics operators in planning their freight service schedules. Numerical results indicate that the developed algorithm is capable of producing optimal solutions efficiently for both small and large intermodal freight networks.